HUMAN BREAST MILK FORTIFICATION WITH SKIMMED MILK AND OLIVE OIL FOR WEIGHT GAIN IN VERY LOW BIRTH WEIGHT NEONATES - Waqqas, Arouj; Ahmed, Zeeshan; Farrukh, Huma; Khalid, Hina; Waqar, Talal (Pakistan Armed Forces Medical Journal, 2021)
Objective: To observe the effect of fortification of expressed human breast milk with olive oil and skimmed milk in improving weight gain in very low birth weight neonates and shortening their length of hospital stay. Study Design: A comparative prospective study. Place and Duration of Study: Combined Military Hospital Lahore, from Mar 2018 to Mar 2019. Methodology: Neonates admitted with very low birth weight and gestational age of <34 weeks were included in study. Sixty babies were enrolled using non-probability consecutive sampling; random number table used to allocate them into a fortifycation group and a control group. The control group received expressed milk alone, while olive oil oneml twice daily and skimmed milk one gram in every third feed were added to expressed milk in the fortification group. Results: The study comprised of 60 neonates, with 30 in each of the groups. Weight gain was 24.83 ± 5.63 in the fortification group and 11.72 ± 3.95 in the control group (p≤0.001). Mean hospital stay was 20.57  16.511 in the fortification group and 27.67 ± 8.89 in the control group (p≤0.043). Conclusion: Olive oil and skimmed milk fortification of breast milk was effective for weight gain and reducing length of hospital stay in very low birth weight neonates.